Single-point ACT2 gene mutation in the Arabidopsis root hair mutant der1-3 affects overall actin organization, root growth and plant development - Vaškebová, L; Šamaj, J; Ovecka, M (Annals of botany, 2018)
BACKGROUND AND AIMS: The actin cytoskeleton forms a dynamic network in plant cells. A single-point mutation in the DER1 (deformed root hairs1) locus located in the sequence of ACTIN2, a gene for major actin in vegetative tissues of Arabidopsis thaliana, leads to impaired root hair development (Ringli C, Baumberger N, Diet A, Frey B, Keller B. 2002. ACTIN2 is essential for bulge site selection and tip growth during root hair development of Arabidopsis. Plant Physiology129: 1464-1472). Only root hair phenotypes have been described so far in der1 mutants, but here we demonstrate obvious aberrations in the organization of the actin cytoskeleton and overall plant development. METHODS: Organization of the actin cytoskeleton in epidermal cells of cotyledons, hypocotyls and roots was studied qualitatively and quantitatively by live-cell imaging of transgenic lines carrying the GFP-FABD2 fusion protein and in fixed cells after phalloidin labelling. Patterns of root growth were characterized by FM4-64 vital staining, light-sheet microscopy imaging and microtubule immunolabelling. Plant phenotyping included analyses of germination, root growth and plant biomass. KEY RESULTS: Speed of germination, plant fresh weight and total leaf area were significantly reduced in the der1-3 mutant in comparison with the C24 wild-type. Actin filaments in root, hypocotyl and cotyledon epidermal cells of the der1-3 mutant were shorter, thinner and arranged in more random orientations, while actin bundles were shorter and had altered orientations. The wavy pattern of root growth in der1-3 mutant was connected with higher frequencies of shifted cell division planes (CDPs) in root cells, which was consistent with the shifted positioning of microtubule-based preprophase bands and phragmoplasts. The organization of cortical microtubules in the root cells of the der1-3 mutant, however, was not altered. CONCLUSIONS: Root growth rate of the der1-3 mutant is not reduced, but changes in the actin cytoskeleton organization can induce a wavy root growth pattern through deregulation of CDP orientation. The results suggest that the der1-3 mutation in the ACT2 gene does not influence solely root hair formation process, but also has more general effects on the actin cytoskeleton, plant growth and development.
Keywords: mutace; aktiny; Actins; Mutation; Plant Roots; kořeny rostlin; Arabidopsis; proteiny huseníčku; Arabidopsis Proteins